Risk factors of late onset sepsis caused by extended spectrum beta-lactamase (ESBL) - producing bacteria in preterm infants - Irene Ratridewi; Savitri Laksmi Winaputri; Eko Sulistijono; Fireka Imsa Sastia Juniantika (Indonesian Pediatric Society, 2023)
Background High incidence of late-onset sepsis (LOS) in preterm infants contributes to neonatal morbidity. Therapeutic outcomes of LOS have deteriorated as a result of increased antibiotic resistance problems, mainly from ESBL isolates. Controlling risk factors is important in reducing morbidity and mortality as well as providing guidance for antibiotic selection. Objectives To determine the risk factors of LOS due to ESBL-producing bacteria in preterm infants. Methods This is a retrospective study. The inclusion criteria was neonates diagnosed with late-onset neonatal sepsis by clinical signs and a positive blood culture. The blood culture result and characteristics patients as secondary data were extracted from medical records within the hospital facilities and the institutional database of the Neonatology Department of Universitas Brawijaya (January 2019 to March 2021). Statistical analysis was done to compare characteristics of the patients in the ESBL positive group to those in the ESBL negative group to assess the potential risk factors. Results Among 124 preterm infants with LOS, 62 of them were ESBL-positive case subjects and the other 62 were non-ESBL-producing control subjects. Gram-negative bacteria were the most common pathogens identified, with 96% (n=59) of them being the ESBL-producing strain, predominated by Klebsiella pneumoniae (n=56). Factors significantly correlated with the occurrence of LOS-ESBL included prior history of invasive procedures (OR 3.13; 95%CI 1.45 to 6.73; P=0.00), central access insertion (OR 9.54; 95%CI 3.7 to 24.2; P=0.00), and parenteral nutrition (OR 6.03; 95%CI 2.77 to 13.16; P=0.00). Central access insertion had the strongest influence (Exp(B) 6.98; P= 0.00). Conclusion Prior invasive procedures, central access insertion, and parenteral nutrition had significant correlations with the occurrence of LOS-ESBL in preterm infants. Central access insertion is a predictive factor for LOS-ESBL.